Fatty Acid and Phytochemical Compositions of Plantago Seed Oils and Their Functionalities. (24th May 2017) - Wang, Yanling; Niu, Yuge; Zhao, Xin; Wang, Bangquan; Jiang, Qianqian; Liu, Jie; Sheng, Yi
Abstract: To develop the potential applications of Plantago plants, seed oils were extracted from 14 cultivars of Plantago around China. Their fatty acid profiles, tocopherols, carotenoid compositions, anti‐inflammatory and antioxidant properties were also investigated. The Plantago seed oils (PSO) were abundant in linolenic acid from 11.12 to 29.36 g/100 g oil and had low fatty acid ratio of n‐6/n‐3 ratio matched with the dietary recommendations. The tocopherol contents of PSO ranged from 693.25 to 3708.80 μg/g and the lutein contents ranged from 2.29 to 26.68 μg/g. The PSO showed significant inhibitory effects on TNF‐α, IL‐1β, and COX‐2 mRNA expression in RAW 264.7 mouse macrophage cells induced by LPS. In addition, the properties on scavenging DPPH, oxygen and hydroxyl radicals indicated that PSO had potential antioxidant properties. The results could develop PSO as novel functional foods to improve human health.